2012
DOI: 10.1159/000342925
|View full text |Cite
|
Sign up to set email alerts
|

An Ergonomic Study of Single-Port versus Multi-Port Laparoscopic Mesh Insertion for Ventral Hernia Repair

Abstract: Purpose: To assess the mental effort and physical discomfort of placement of a prosthetic mesh into the abdominal cavity with single-incision laparoscopic surgery (SILS) or multi-port laparoscopic access for incisional ventral hernia repair. Methods: A total of 10 surgeons with previous experience in conventional laparoscopic surgery performed four surgical tasks through a multi-port laparoscopic access and a SILS access in a porcine model during a first 4-hour working session and a second 2-hour working sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This trend has led to trials of single incision techniques for both the transabdominal preperitoneal (TAPP) and totally extraperitoneal (TEP) approaches [2,[4][5][6][7]. However, single incision laparoscopic surgery (SILS) has met with some resistance because of limitations including the difficult ergonomics of single incision instruments, the reported increase in port-site herniation following SILS, and the relatively steep learning curve [8][9][10]. It may be these challenges that have precluded the widespread adoption of SILS in laparoscopic inguinal hernia repair.…”
Section: Introductionmentioning
confidence: 99%
“…This trend has led to trials of single incision techniques for both the transabdominal preperitoneal (TAPP) and totally extraperitoneal (TEP) approaches [2,[4][5][6][7]. However, single incision laparoscopic surgery (SILS) has met with some resistance because of limitations including the difficult ergonomics of single incision instruments, the reported increase in port-site herniation following SILS, and the relatively steep learning curve [8][9][10]. It may be these challenges that have precluded the widespread adoption of SILS in laparoscopic inguinal hernia repair.…”
Section: Introductionmentioning
confidence: 99%
“…A recent experimental study clearly demonstrated a significantly greater physical and mental effort is required to conduct the procedure through a single access portal, even among individuals with considerable previous experience with standard laparoscopic techniques (López‐Cano et al . ).…”
mentioning
confidence: 97%